2020
DOI: 10.1039/d0ra06607a
|View full text |Cite
|
Sign up to set email alerts
|

Changes of pro-inflammatory and anti-inflammatory macrophages after peripheral nerve injury

Abstract: The temporal patterns of pro-inflammatory and anti-inflammatory macrophages after peripheral nerve injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
(43 reference statements)
0
12
0
Order By: Relevance
“…[44] In vivo implantation of M2 macrophages promoted SCs migration and stimulated SCs infiltration through miRNAs carried in microvesicles, which both favor axon regeneration. [35] Conversely, implantation of M1 macrophages did not show similar beneficial effects. [35,58,61] Therefore, M2 macrophages not only affect the SCs but also affect nerve repair.…”
Section: Mids Facilitate Microenvironment Reconstruction By Scs and M...mentioning
confidence: 96%
See 2 more Smart Citations
“…[44] In vivo implantation of M2 macrophages promoted SCs migration and stimulated SCs infiltration through miRNAs carried in microvesicles, which both favor axon regeneration. [35] Conversely, implantation of M1 macrophages did not show similar beneficial effects. [35,58,61] Therefore, M2 macrophages not only affect the SCs but also affect nerve repair.…”
Section: Mids Facilitate Microenvironment Reconstruction By Scs and M...mentioning
confidence: 96%
“…[35] Conversely, implantation of M1 macrophages did not show similar beneficial effects. [35,58,61] Therefore, M2 macrophages not only affect the SCs but also affect nerve repair. We confirmed that macrophage aggregation enhanced the proliferation and migration of SCs to some extent.…”
Section: Mids Facilitate Microenvironment Reconstruction By Scs and M...mentioning
confidence: 96%
See 1 more Smart Citation
“…These reactions lead to a significant decrease in the number of new central nuclear myotubes and in the volume of regenerated muscle fibers, leading to necrosis sexual muscle fibers while inflammatory cell infiltration increased significantly. Research by Zhang et al (2020a) ; Zhang et al (2020b) showed that endothelial cells initiate lactate shuttle through glycolysis products during ischemia, which polarizes macrophages to M2 type and secretes a large amount of VEGF, which strengthens the positive feedback loop of angiogenesis, improves the density of angiogenesis, and promotes muscle revascularization. In addition, VEGF can also contribute to the muscle regeneration by inducing the proliferation and differentiation of myogenic progenitor cells of skeletal muscle.…”
Section: Macrophages and Tissue Regenerationmentioning
confidence: 99%
“…Previous studies have mostly focused on the observation and description of the phenotype, morphology, and mechanism of macrophages that promote tissue damage by inducing an immune response ( Rayees et al, 2020 ; Zhang et al, 2020a ; Zhang et al, 2020b ; Li et al, 2021a ; Li et al, 2021b ). With the gradual development of regenerative medicine and modern molecular biology, recent studies have found that macrophages play an important role in promoting the regeneration of different tissues such as the heart, liver, kidney, muscle, and nerve.…”
Section: Introductionmentioning
confidence: 99%